2002
DOI: 10.1113/jphysiol.2001.013439
|View full text |Cite
|
Sign up to set email alerts
|

Specific localization of an inwardly rectifying K+ channel, Kir4.1, at the apical membrane of rat gastric parietal cells; its possible involvement in K+ recycling for the H+‐K+‐pump

Abstract: Hydrochloric acid (HCl) is produced in parietal cells of gastric epithelium by a H+‐K+ pump. Protons are secreted into the gastric lumen in exchange for K+ by the action of the H+‐K+‐ATPase. Luminal K+ is essential for the operation of the pump and is thought to be supplied by unidentified K+ channels localized at the apical membrane of parietal cells. In this study, we showed that histamine‐ and carbachol‐induced acid secretion from isolated parietal cells monitored by intracellular accumulation of aminopyrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 37 publications
1
54
0
3
Order By: Relevance
“…However, Fujita et al (12) found several members of the Kir family of inwardly rectifying K ϩ channels expressed in rat gastric mucosa, and this was confirmed by others (9,13,14). The only study in which PC tubulovesicular and secretory membranes were isolated, reconstituted in lipid bilayer, and studied electrophysiologically found channels with Kir rather than KCNQ1 channel properties (13).…”
supporting
confidence: 50%
See 1 more Smart Citation
“…However, Fujita et al (12) found several members of the Kir family of inwardly rectifying K ϩ channels expressed in rat gastric mucosa, and this was confirmed by others (9,13,14). The only study in which PC tubulovesicular and secretory membranes were isolated, reconstituted in lipid bilayer, and studied electrophysiologically found channels with Kir rather than KCNQ1 channel properties (13).…”
supporting
confidence: 50%
“…When colocalization of Kir4.1 with the H ϩ /K ϩ -ATPase in the tubulovesicles as well as the stimulated secretory membranes had been observed (12)(13)(14), we and others believed that Kir4.1 channels may serve to bring K ϩ to the extracellular K ϩ -binding site of the H ϩ /K ϩ -ATPase during stimulation of acid secretion. In this scenario, the acid secretory rate should be decreased in Kir4.1 KO mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In the contexts of LR asymmetry and mammalian gastric tissues, the Kir4.1 K ϩ channel is a required partner for the physiological activity of the H ϩ K ϩ ATPase (Fujita et al, 2002;Levin et al, 2002;Chen and Levin, 2004). Correspondingly, we conducted a preliminary screen to identify potential types of channels involved in regulating LR asymmetry in Ciona (Table 1).…”
Section: Blocker Disrupts Asymmetric Gene Expression In Cionamentioning
confidence: 99%
“…With respect to the basic physiology of the cell, H,K-ATPases contribute to the electrochemical potential mostly through establishing a proton gradient, as the H ϩ /K ϩ antiport is electrically neutral. However H,K-ATPases may act together with a K ϩ channel to result in a net loss of positive charges (Fujita et al, 2002 drives asymmetric Calcium concentrations and activation of Notch signaling during initiation of LR asymmetry. A model has been suggested in which an electrochemical gradient along the left-right axis drives asymmetric Calcium distribution to high levels of Ca 2ϩ on the left side, which in turn activates Notch signaling (Raya et al, 2003(Raya et al, , 2004.…”
Section: Discussionmentioning
confidence: 99%